The role of knowledge of HIV/AIDS amongst employees in a non-governmental organization - Parsard Beharie, Phoolmatie (Milla) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.